Analysis of CO, CO2 and NO2 airpollutants in the city of Villavicencio - Colombia (2023)
The article summarizes the results of research, whose purpose was to characterize the behavior of gases NO2, CO, CO2 present in the city of Villavicencio Meta Colombia. The methodology used was experimental type whose data were processed using descriptive statistical techniques. The results indicated that the gases under study are in the permissible levels by current legal regulations and recommended continued efforts to mitigate the agentsair pollutants in the city. © International Research Publication House.